PENGARUH DISIPLIN KERJA, PENGALAMAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT KUMALA INDONESIA SHIPYARD - Amalia, Suci; Siagian, Mauli (LPPM Universitas Putera Batam, 2020)
Human resources are main resources in an organization that functions as main organization and the activities of the organization as well as one of the main spearheads for each organization's operations. And besides increasing human resources also required aspects of the company that are needed to provide knowledge well to carry out direction of the organization. Purpose of this study was to study the partial and simultaneous interaction of work discipline variables, work experience, and organizational culture on employee performance at PT Kumala Indonesia Shipyard. This quantitative study used sampling technique of 107 participants. Data collection was carried out by questionnaire interviews with all respondents using a Likert scale as a measurement scale and SPSS Version 22 as a data processing application. As a result of the T-Test, the partial variables of work coordination, work experience, and organizational culture have a positive and significant influence on the performance of the employees of PT Kumala Indonesia Shipyard. And results of the F Test states that simultaneous work variables and positive and significant work experience on employee performance, work experience and simultaneous organizational culture have a positive and significant effect on employee performance.